Iatrogenic Damage to the Radial Nerve During Osteosynthesis of the Humerus. Prevention, Diagnosis and Treatment - Y. A. Bogolyubsky; A. M. Fayn; A. V. Sachkov; I. I. Mazhorova; A. Y. Vaza; R. S. Titov; V. B. Bondarev; A. Y. Sergeyev (Неотложная медицинская помощь, 2020)
THE RELEVANCE is determined by the significant frequency of iatrogenic injuries of the radial nerve during internal osteosynthesis of the humerus, long-lasting functional disorders, a large number of unsatisfactory results, as well as the lack of a unified approach to diagnosis and treatment.MATERIAL AND METHODS. The causes of iatrogenic damage to the radial nerve were studied in 22 patients who underwent internal fixation during fractures of the humeral diaphysis. The ultrasound examination was used to visualize the radial nerve. In 13 patients (59.1%), a pathogenetic treatment was used, including medication, physical and mechanical therapy.RESULTS AND DISCUSSION. In plate osteosynthesis, a greater number of iatrogenic damage to the radial nerve was observed than during osteosynthesis with screws. The ultrasound method had high diagnostic values to determine the continuity of the nerve trunk and identify conflicts with solid structures. The use of pathogenetic therapy of neuropathy led to a more rapid clinical recovery of limb function.CONCLUSION. To prevent iatrogenic injuries and avoid gross manipulations, the access with sufficient visualization of the radial nerve is necessary in plate osteosynthesis and distal blocking outside the projection of the radial nerve is necessary in intramedullary osteosynthesis. Indications for early revision after iatrogenic damage are neurotmesis and a nerve conflict with bone fragments or an implant.